A Questão do Financiamento e Precarização do Ensino na EAFB/PE na Década de 90 - Reis Gouveia, Karla (Boletim Técnico do Senac, 2006)
This article is part of research for a master’s degree that sought to analyze the implications of the vocational training reform of the 1990s at the Federal Agrotechnical School of Barreiros/EAB (Pernambuco state). The research laid bare that the problematic of fi nancing, or lack of investments in material and human resources to implement the reform, was one of factors that strongly contributed to precarization and loss of qualifi cation of teaching in the referenced educational institution.